Studi Korelasi Metode Silent Sitting Dan Meditasi Cahaya Terhadap Konsentrasi Belajar Siswa Di Sekolah Dasar Sathya Sai Denpasar - Kompyang Sri Wahyuningsih; I Ketut Sudarsana; Heny Perbowosari (Jayapangus Press, 2021)
The purpose of this research is to analyze the comparison between the theory obtained in college and the reality in the field. The specific objective was to analyze the relationship between Silent Sitting and Light Meditation on the concentration of student at SD Sathya Sai Denpasar. This research uses observation, interview and questionnaire methods with data collection instruments in the form of questionnaires and statistical analysis methods with multiple regression analysis formulas. The research sample used a sampling technique (proportional random sampling) with a sample size of 23 students. Processing data using multiple regression analysis formulas and data analysis using computer assistance through the SPSS version 11.00 for Windows. The rule of the decision is to use a significance level (a 0.05), if r count is more> t table, then Ho is rejected, meaning there is a significant relationship. Conversely, if r count <t table, then Ho is accepted, it means that there is no significant relationship. The findings of the research, the coefficient of determination (R²) = 0.64. Guided by the correlation coefficient interpretation table, the value of 0.64 states that there is a strong relationship between variables. This means that the relationship between Silent Sitting and Light Meditation on the concentration of student at SD Sathya Sai Denpasar is strong. The contribution of Silent Sitting and Light Meditation methods is 64%. Thus, it can be concluded that the Silent Sitting and Light Meditation methods can make students concentrate on learning.